Use of Foley catheter as a flap retainer - Hemant Saraiya (Indian Journal of Plastic Surgery)
keeping skin graft or a flap adherent to the underlying surface can sometimes be a difficult job, particularly inside a cavity. different methods have been used for this function with varying success but the search is still on for an ideal pressure dressing.